ContFree-NGS: Removing Reads from Contaminating Organisms in Next Generation Sequencing Data - Peres, Felipe Vaz; Riaño-Pachón, Diego Mauricio (Anais do Simpósio Brasileiro de Bioinformática (BSB), 2021)
We present ContFree-NGS, an open source software that removes reads originating from contaminant organisms in your sequencing dataset. The user has to provide a target taxon, and anything that does not belong to this taxon or its descendants will be labelled as contaminant. In order to achieve this, ContFree-NGS exploits results from a taxonomy assignment engine, like Kraken2 or Kaiju.